2003
DOI: 10.1507/endocrj.50.801
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with ACE (Angiotensin Converting Enzyme) Develops Diabetic Changes in the Kidney and Retina in Diabetogenic Rats

Abstract: Abstract. In normal New Zealand white rabbits, immunization with rabbit lung ACE (angiotensin converting enzyme) induced atherosclerotic retinal changes, and glomerular changes similar to those seen in diabetic nephropathy. Also, in genetically diabetogenic rats, immunization with the rabbit lung ACE induced diabetic nephropathy and retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…Recently, the possibility of autoantibodies to ACE in diabetic patients has been suggested (35). The same group also demonstrated that immunization of rabbits and rats with ACE led to the development of atherosclerotic retinal changes and glomerular changes similar to those seen in diabetic nephropathy (36). Bearing in mind the presence of several mouse models of diabetes, awareness of the potential loss of natural antigenicity or the appearance of non‐natural epitopes on mouse ACE by minor denaturation during an adsorption on plastic will be essential for searching for autoantibodies to mouse ACE in these mouse models.…”
Section: Discussionmentioning
confidence: 83%
“…Recently, the possibility of autoantibodies to ACE in diabetic patients has been suggested (35). The same group also demonstrated that immunization of rabbits and rats with ACE led to the development of atherosclerotic retinal changes and glomerular changes similar to those seen in diabetic nephropathy (36). Bearing in mind the presence of several mouse models of diabetes, awareness of the potential loss of natural antigenicity or the appearance of non‐natural epitopes on mouse ACE by minor denaturation during an adsorption on plastic will be essential for searching for autoantibodies to mouse ACE in these mouse models.…”
Section: Discussionmentioning
confidence: 83%
“…These findings are particularly relevant with respect to the concepts and standardization of immunoassays in which human ACE antigen will be used. Nishida et al (49) suggested the possibility of auto‐antibodies to ACE in diabetic patients and also showed that immunization of rabbits and rats with ACE led to the development of atherosclerotic retinal and glomerular changes similar to those seen in diabetic nephropathy (50). The extremely high sensitivity of mAb 3C5, which can recognize 1–2 ng of human ACE in Western blotting, raises the possibility of detecting and quantifying human ACE in biological fluids, such as cerebrospinal fluid (51) or urine (52, 53), without the need for enrichment (27, 28).…”
Section: Discussionmentioning
confidence: 99%
“…The antibodies were positive for 64.5% of the patients with diabetes and were positive in 83.3% in the early stage of clinical diabetic nephropathy. In addition, in genetically diabetogenic OLETF ( Otsuka Long-Evans Tokushima Fatty ) rats 2 , one of the characteristics of which strain is spontaneous nephropathy resembling those of human type 2 diabetes, and in control LETO rats 2 , immunization with rabbit lung ACE developed glomerulopathy similar to that seen in diabetics 3 . Also, in normal New Zealand white rabbits, immunization with the rabbit lung ACE induced glomerular changes similar to those seen in diabetic nephropathy 3 .…”
mentioning
confidence: 99%
“…In addition, in genetically diabetogenic OLETF ( Otsuka Long-Evans Tokushima Fatty ) rats 2 , one of the characteristics of which strain is spontaneous nephropathy resembling those of human type 2 diabetes, and in control LETO rats 2 , immunization with rabbit lung ACE developed glomerulopathy similar to that seen in diabetics 3 . Also, in normal New Zealand white rabbits, immunization with the rabbit lung ACE induced glomerular changes similar to those seen in diabetic nephropathy 3 . In this study, renal tissues identical to those examined in research of diabetic nephropathy by PAS staining and electron microscope in preceding study 3 , were examined by immunostaining methods, only to prove that the diabetic glomerular changes may occur by immunization with ACE, not by non-specific responses to ACE, in non-diabetogenic rats and rabbits.…”
mentioning
confidence: 99%
See 1 more Smart Citation